Antecedents and consequence of green knowledge: a study of green cosmetics / Biru Ayu Maharani and Ayu Ekasari - Maharani, Biru Ayu; Ekasari, Ayu (Universiti Teknologi MARA, Selangor, 2022)
This research aims to study the impact of cosmopolitanism, global self-identity and online communities on green knowledge as well as the effect of green knowledge on green trust. A total of 200 consumers of green cosmetics participated in the online survey. Data were analyzed using structural equation modelling technique. The obtained results found that cosmopolitanism and online communities influence green knowledge significantly, while global self-identity has no significant influence in this study. The findings offer directions to green cosmetics marketers in understanding the factors that form green knowledge of green cosmetics. Also, this study suggests that firms can design marketing communications by linking these factors with green knowledge and trust towards green cosmetics. However, the research has several drawbacks. Future studies should add the numbers of respondents and green brands to be studied to increase its generalizability. This research contributes to existing literature in green marketing by incorporating globalization and digital issues that influence green knowledge and later, green trust.